Qatar : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2019)
This Selected Issues paper focuses on policies to drive diversification for Qatar. Diversification is important for a large commodity exporter like Qatar: it helps manage temporary shocks and prepare for sweeping changes to the economic setting. Qatar's large financial holdings can help diversify revenues. Both structural reforms to improve the business environment and sector-specific policies can support diversification of activity and exports. Sector-specific policies should build on existing economic strengths in areas with room for exports and innovation. Emphasis should be placed on developing expertise in specific clusters. Export markets and competition provide crucial mechanisms to ensure discipline. Further diversification is important to help Qatar manage temporary shocks and prepare for far-reaching shifts to the economic context. Well-targeted, structured, and sequenced policies to encourage specific sectors can also play a role in diversifying Qatar's economy. Export markets and competition should be deliberately used to hold recipients of support accountable. Policies to encourage specific sectors have resulted in little more than inefficient import substitution in many countries. Avoiding this outcome requires discipline: support should be withdrawn in the absence of progress.